2014
DOI: 10.1590/1807-3107bor-2014.vol28.0035
|View full text |Cite
|
Sign up to set email alerts
|

Amelogenin gene influence on enamel defects of cleft lip and palate patients

Abstract: The aim of this study was to investigate the occurrence of mutations in the amelogenin gene (AMELX) in patients with cleft lip and palate (CLP) and enamel defects (ED). A total of 165 patients were divided into four groups: with CLP and ED (n=46), with CLP and without ED (n = 34), without CLP and with ED (n = 34), and without CLP or ED (n = 51). Genomic DNA was extracted from saliva followed by conducting a Polymerase Chain Reaction and direct DNA sequencing of exons 2 through 7 of AMELX. Mutations were found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…15,35,36 Genetics-based studies have shown that amelogenin (encoded by the AMELX gene), which is involved in the formation of dental enamel, is also a candidate gene for involvement in CLP, which suggests a genetic association (or shared genetic background) linking enamel defects and clefts. 37 Thus, the inclusion of information related to dental anomalies in genetic analyses of CLP may provide new opportunities to map the susceptibility loci associated with the production of clefts.…”
Section: Discussionmentioning
confidence: 99%
“…15,35,36 Genetics-based studies have shown that amelogenin (encoded by the AMELX gene), which is involved in the formation of dental enamel, is also a candidate gene for involvement in CLP, which suggests a genetic association (or shared genetic background) linking enamel defects and clefts. 37 Thus, the inclusion of information related to dental anomalies in genetic analyses of CLP may provide new opportunities to map the susceptibility loci associated with the production of clefts.…”
Section: Discussionmentioning
confidence: 99%
“…Other constituents of citrus peels include essential oils which have lipolytic, antimicrobial, antioxidant and antiinflammatory effects; (Hyang-Sook, 2006;Kanaze et al, 2008;Oliveira et al, 2014) and also vitamin C which contributes to effective digestion and weight loss by increasing acidity thereby increasing calcium assimilation No negative side effects were reported in previous work in the animals that were fed with PMFs. However, in this work, the animals showed signs of tremor and exfoliation of fur for SY, OR and GR groups, both in the second week.…”
Section: Resultsmentioning
confidence: 99%
“…Embriologically, the formation of tooth germs and the occurrence of cleft defects have a close relationship in terms of timing, thus factors leading to cleft could also affect the dental development [7,8] . In this context, recent studies have confirmed that genetic mutations (Interferon Regulatory Factor 6, Msh homeobox 1, Paired Box gene 9 and Transforming Growth Factor-beta) related to oral cleft lead to selective hypodontia and that Amelogenin X isoform gene, involved in the formation of the dental enamel, could also be involved in the development of clefts, suggesting a genetic association between dental anomalies and clefts [9,10] .…”
Section: Introductionmentioning
confidence: 92%